Effectiveness and Constitutional Standards as a Barrier to the Correct Implementation of the European General Anti-abuse Rule (Polish Yearbook of International Law, 2025)
A key element in the fight against tax avoidance within the European Union has been the obligation for all Member States to introduce a harmonised general anti-abuse rule (GAAR). This article explores the interplay between the Polish constitutional standards regarding the GAAR, the need to ensure its effectiveness and EU standards derived from Art. 6 of the ATA Directive and the case law of the Court of Justice of the European Union (CJEU). The analysis concludes that, while the subjective test was implemented correctly, Poland failed to properly implement Art. 6 of the ATA Directive in relation to the genuine activity test and the objective test. The Constitutional Tribunal established a very high standard for the protection of taxpayers’ rights, which hinders the proper implementation of the GAAR and conflicts with the case law of the CJEU and the provisions of the ATA Directive. Keywords: general anti-abuse rule, GAAR, constitutional standards, ATA Directive, CJEU case law, incorrect implementation, effectiveness.